Políticas públicas e os desafios da educação de surdos - Jesus, Pablo José Corrêa de (Universidade Federal do Tocantins, 2022)
This paper focuses on a study about the current public policies that guide the Education of the Deaf in Brazil, provided for in Law No. 10.436 / 2002, Decree No. 5.626 / 2005 and National Education Plan (2014-2024) and their main challenges. This discussion is necessary so that deaf education in Brazil is not, as it was for many years, the object of postponement. The objective was to point out some of the challenges that must be faced in view of the new legal guidelines. The research was of a qualitative nature, of the bibliographic type. The main result observed from the literary review, is that even considering the whole legal framework that In the case of deaf education from a bilingual perspective, it will only be effectively realized if the perception of the deaf subject ceases to be deficient, abnormal, and from the anthropological point of view, ie, the cultural subject and multifaceted identities.